Recovery of microquantities of human Epidermal Growth Factor from Esherichia coli homogenate and Pichia pastoris culture medium using expanded bed adsorption - Rosti, Ira Amira; Ramanan, Ramakrishnan Nagasundara; Tan, Joo Shun; Ling, Tau Chuan; Ariff, Arbakariya (Taylor & Francis Inc., 2014)
A rational design of recovery of microquantities of human Epidermal Growth Factor (hEGF) from different complex feedstocks using STREAMLINE Direct HST in expanded bed adsorption (EBA) was approached. The highest adsorption yields were achieved at pH 4.5, which was close to the isoelectric point of protein by utilizing mixed interaction that was offered by the adsorbent. Escherichia coli treated with osmotic shock and Pichia pastoris culture medium spiked with hEGF were applied as feedstocks to evaluate bed stability in the presence of cells. A recovery of 90% was achieved for both cells at pH 4.5. Effects of pH on the P. pastoris culture medium and E. coli homogenate were similar, indicating that both cells have negatively charged surfaces at pH 4.5. The cell transmission index (T) showed that there was no tendency for E. coli homogenate and yeast cells to bind to the matrix at pH 4.5. Because the electrostatic properties of cells and protein are pH dependent, the method presented for screening conditions for biomass and adsorbent is convenient for designing robust and reliable EBA purification processes. Lower ionic strength improved purification of hEGF from E. coli homogenate.